A Pragma-Forensic Study of Advertisement Fraud: Applying Grice’s Implicature and Shuy’s Analysis - Igaab, Zainab Kadim; Mohammed, Haneen Shawqi (Indian Journal of Information Sources and Services, 2026)
This study focuses on the pragmatic and forensic aspects of fraud. It is based on questions regarding the characteristics of advertisement fraud in terms of implicature, schema, agenda, speech acts, and conversational strategies. It has been hypothesized that assertive and commissive speech acts are mostly performed in fraudulent advertisements. One of the conversational strategies, repetition, is continuously employed by fraudsters in the advertisement field. Third, Grice’s quality maxim is strongly assumed to be the most frequently breached maxim. The data consisted of advertisements for two weight loss products. These advertisements are presented as exhibit files in the fraud case 2:16-cv-00023-GZS. The data were retrieved from (www.ftc.gov). The model of the study consists of Shuy’s analysis with all its steps and Grice’s implicature theory. After a detailed discussion and analysis, it was concluded that advertisement fraudsters perform indirect commissive speech acts to avoid direct liability, and they perform direct requests as a way of showing authority. The fraudster’s goal is to hide information that has negative effects, so fewer details are provided about the product. By contrast, the fraudster pours irrelevant information that deceitfully adds legitimacy to the advertisement, which is a big red flag.